1990
DOI: 10.1017/s0031182000063241
|View full text |Cite
|
Sign up to set email alerts
|

Low-dose oral administration of human interferon alpha can control the development ofTheileria parvainfection in cattle

Abstract: Two natural human interferon alpha preparations, (nHuIFN-alpha [Cantell]) and (nHuIFN-alpha [ISI]), were used for the oral treatment of cattle experimentally infected with Theileria parva parva. In the first experiment, 8 Friesian bulls were inoculated with a 1 in 10 dilution of a sporozoite stabilate of T.p. parva (Marikebuni) stock. Four of the cattle were treated daily with 1 international unit/kg body weight (i.u./kg bwt) of nHuIFN-alpha (Cantell) from day -2 to day 8 p.i. None of the 4 calves given IFN de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

1991
1991
1999
1999

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…An intriguing aspect of these findings is that the therapeutic effect was seen after oral administration of macromolecular proteins. In addition to certain cytokines that have been shown to exert systemic effects after oral application [8][9][10][11][12][13][14], the feeding of enzymes now seems to be suited to the induction of systemic effects. Trypsin, a constituent of Phlogenzym, is actively imported from the gut [15][16][17][18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An intriguing aspect of these findings is that the therapeutic effect was seen after oral administration of macromolecular proteins. In addition to certain cytokines that have been shown to exert systemic effects after oral application [8][9][10][11][12][13][14], the feeding of enzymes now seems to be suited to the induction of systemic effects. Trypsin, a constituent of Phlogenzym, is actively imported from the gut [15][16][17][18].…”
Section: Discussionmentioning
confidence: 99%
“…For example, the feeding of interferon-(IFN-) confers protection from collageninduced arthritis and reduces the collagen-specific delayed-type hypersensitivity response [9]. Oral administration of IFN-also ameliorates infectious diseases caused by vesiculo stomatitis virus [10], feline leukemia virus [11] and Theileria infection [12]. Oral, but not parenteral interleukin-12 (IL-12) was effective in redirecting the T helper 2 (Th2) responses to tetanus toxoid towards a Th1-type response [13], and oral administration of IL-6 was shown to enhance the systemic immune response against Campylobacter infection and, upon rechallenge, protection from it [14].…”
Section: Introductionmentioning
confidence: 99%
“…The relationship between the minimum PCV and the minimum leukocyte count of the animal over the sampling period with the level of T. parva infection in ticks is important. Leukopenia is a common change associated with T. parva infection and it can provide an index of the severity of disease (Neitz, 1957;Dolan et al 1984;Young et al 1990). Hence a decrease in leukocyte count and its degree defines the severity of infection which has been shown here to affect the level of infection developing in the tick.…”
Section: Discussionmentioning
confidence: 73%
“…Symptomatic HIV-positive patients treated for at least 6 weeks showed 'a dramatic alleviation of clinical symptoms' and in 20% of patients serology became negative for HIV, with this unexpected serodeconversion being apparently due to rapid clearance of anti-HIV serum antibodies (Koech et al 1990). Other studies, examining enhancement of vaccine efficiency (Cummins & Hutcheson 1986) or the prevention of clinical Theileria parva infection (Young et al 1990) in calves or in colostrum-deprived newborn piglets challenged either with Group A rotavirus (Lecce et al 1990) or with transmissible gastroenteritis virus (Cummins et al 1991), have shown that animals treated with oral low-dose human natural IFNa had a lower viral excretion, enhanced antibody titre, increased survival and greater weight gain than control groups. Other studies, examining enhancement of vaccine efficiency (Cummins & Hutcheson 1986) or the prevention of clinical Theileria parva infection (Young et al 1990) in calves or in colostrum-deprived newborn piglets challenged either with Group A rotavirus (Lecce et al 1990) or with transmissible gastroenteritis virus (Cummins et al 1991), have shown that animals treated with oral low-dose human natural IFNa had a lower viral excretion, enhanced antibody titre, increased survival and greater weight gain than control groups.…”
Section: Mechanisms 0/ Action and Evidence 0/ Beneficial Effectsmentioning
confidence: 99%